Analisis Profitabilitas, Likuiditas, dan Ukuran Perusahaan Sebagai Determinan Kebijakan Dividen Korporasi - Muhamad Rizal Suprayitno; Wulan Suryandani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study aims to examine the effect of profitability, liquidity, and firm size on dividend policy in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research is motivated by inconsistencies in the findings of previous studies and fluctuations in the average Dividend Payout Ratio (DPR) within the food and beverage sector. A quantitative research approach was employed using multiple linear regression analysis with SPSS version 22. The research sample consisted of 25 companies selected through purposive sampling based on specific criteria to ensure the suitability of the sample with the research objectives. Dividend policy was measured using the Dividend Payout Ratio (DPR), while profitability was proxied by Return on Assets (ROA), liquidity was measured by the Current Ratio (CR), and firm size was measured using Firm Size. The results of the study indicate that profitability has a negative and insignificant effect on dividend policy, liquidity has a positive but insignificant effect on dividend policy, while firm size has a negative and significant effect on dividend policy. This study is expected to contribute to the development of dividend policy literature and provide practical insights for investors and corporate management in making investment decisions and managing corporate financial performance.